2022
DOI: 10.1007/s11005-022-01541-2
|View full text |Cite
|
Sign up to set email alerts
|

Super topological recursion and Gaiotto vectors for superconformal blocks

Abstract: For any (possibly singular) hyperelliptic curve, we give the definition of a hyperelliptic refined spectral curve and the hyperelliptic refined topological recursion, generalising the formulation for a special class of genus-zero curves by Kidwai and the author, and also improving the proposal by Chekhov and Eynard. Along the way, we uncover a fundamental geometric structure underlying the hyperelliptic refined topological recursion and investigate its properties -parts of which remain conjectural due to compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It is shown that the fundamental structure underlying the topological recursion is a set of equations relating different ω g,n 's called abstract loop equations [32]. This approach has made it possible to generalize topological recursion in several directions, e.g., blobbed topological recursion [33], topological recursion with higher-order ramifications [34,35], and supersymmetric topological recursion [36,37,38]. Kontsevich and Soibelman proposed an algebraic approach to solve abstract loop equations in terms of so-called Airy structures [39,40] which established a new research direction between topological recursion and vertex operator algebras [35,36,37,38,41].…”
Section: Topological Recursionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that the fundamental structure underlying the topological recursion is a set of equations relating different ω g,n 's called abstract loop equations [32]. This approach has made it possible to generalize topological recursion in several directions, e.g., blobbed topological recursion [33], topological recursion with higher-order ramifications [34,35], and supersymmetric topological recursion [36,37,38]. Kontsevich and Soibelman proposed an algebraic approach to solve abstract loop equations in terms of so-called Airy structures [39,40] which established a new research direction between topological recursion and vertex operator algebras [35,36,37,38,41].…”
Section: Topological Recursionmentioning
confidence: 99%
“…We will show that the contribution of (A.22) at each ramification point is symmetric. As explained in [39,35,37,38], in a neighbourhood of r ∈ R, ω 0,2 is expanded in a local coordinate z…”
Section: Appendix a Proofs Of Lemmasmentioning
confidence: 99%
See 1 more Smart Citation